Pengaruh Literasi Keuangan dan Sikap Keuangan terhadap Perilaku Konsumtif Belanja Online Melalui Locus of Control sebagai Variabel Mediasi - Andrea Nur Hidayah; Sartika , Farahiyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine and analyze the influence of financial literacy on consumptive behavior, the influence of financial attitudes on consumptive behavior, the role of locus of control in mediating the influence of financial literacy on consumptive behavior, and the role of locus of control in mediating the influence of financial attitudes on consumptive behavior. The research method used is a quantitative research method with primary data obtained from questionnaire data which is measured using a Likert scale. The population in this study were students from the Faculty of Economics, UIN Malang, class 2020 and 2021, totaling 1039 students. The sampling method used in this research was the proportional random sampling method, so that a sample of 91 respondents was obtained. This research data was obtained from distributing questionnaires which were then processed using SmartPLS 4.0 software. The results of this research show that financial literacy has a positive and significant effect on consumer behavior, financial attitudes have a positive and significant effect on consumptive behavior, locus of control mediates the effect of financial literacy on consumptive behavior, and locus of control mediates the effect of financial attitudes on consumptive behavior. Keywords: Financial Literacy, Financial Attitude, Consumptive Behavior, Locus of Control.